Out-of-plane in situ cyclic testing of unreinforced stone masonry walls with distributed loads - Costa, A. (2013)
The present paper reports an in situ experimental test campaign carried out on existing buildings, in order to investigate the seismic behaviour of traditional masonry walls subject to out-of-plane loads. For the testing proposes, an experimental test setup based on a selfequilibrated scheme was developed and optimized to be applied in situ in two specimens on original and strengthened conditions. The obtained results are presented and carefully discussed namely from the reinforcement solutions’ efficiency point-of-view, as well as compared to previous experimental data obtained for the same type of masonry walls. Additionally, a simplified linearized displacement-based procedure was adapted in order to characterize the nonlinear force-displacement relationship for unreinforced traditional masonry walls and to analytically predict the experimental test results. The confrontation between the experimental and the analytical results are presented and discussed.